The contribution of early auditory and visual information to the discrimination of shot power in ball sports. (July 2017) - Sors, Fabrizio; Murgia, Mauro; Santoro, Ilaria; Prpic, Valter; Galmonte, Alessandra; Agostini, Tiziano
Abstract: Objective: It is well-established that early visual information has an important role in human ability to play ball sports, as its correct interpretation promotes accurate predictions concerning the ball motion. Other research highlights that auditory information provides relevant cues in various sport situations. The present study combines these two lines of research with the aim to investigate the contribution of early auditory and visual information to the discrimination of shot power in sport-specific situations. Design: Two experiments were run, one concerning soccer penalty kicks and the other concerning volleyball smashes. In both experiments there were three conditions: Audio, Audiovideo, and Video; a within subjects design was used, with the three conditions carried out in three different days and in a counterbalanced order among participants. Method: Participants' task was to discriminate the power of two penalties/smashes presented in rapid sequence, on the basis of a two-alternative forced choice paradigm. Results: The results revealed that, for both penalties and smashes, response accuracy was above chance level in all the three conditions; moreover, while for the penalties no difference among the conditions was observed, for the smashes participants were more accurate in the Audio and Audiovideo conditions compared to the Video condition. As concerns the response times, for both penalties and smashes participants were faster in the Audio and Audiovideo conditions compared to the Video condition. Conclusions: Taken together, the results suggest that the discrimination of shot power was more easily performed on the basis of early auditory information than on the basis of the respective visual information. Highlights: Early auditory information alone is sufficient to discriminate shot power above chance. Early visual information alone is sufficient to discriminate shot power above chance. For smashes, discrimination is more accurate in presence of early auditory information. Early auditory information promotes faster discriminations of shot power.